Smilax china L. Polysaccharide Alleviates Oxidative Stress and Protects From Acetaminophen-Induced Hepatotoxicity via Activating the Nrf2-ARE Pathway - Wang, Kaiping; Yang, Linlin; Zhou, Jing; Pan, Xianglin; He, Zihao; Liu, Junxi; Zhang, Yu (Frontiers in Pharmacology, 2022)
The alleviation of oxidative stress is considered an effective treatment for acetaminophen (APAP)-induced acute liver injury (AILI). However, it remains unknow whether the potential antioxidant Smilax china L. polysaccharide (SCLP) protects against AILI. In this study, in vitro and in vivo experiments were conducted to verify the hepatoprotective effect of SCLP against AILI and explore the potential mechanism. We found that SCLP relieved liver histopathological changes; reversed the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA) and reactive oxygen species (ROS); reversed the change in liver myeloperoxidase (MPO) activity; and enhanced liver antioxidant (GSH, GSH-Px and t-SOD) levels in APAP-treated mice, thereby significantly reducing APAP-induced liver toxicity. SCLP rescued the cell viability and alleviated oxidative stress in H2O2-treated mouse AML12 hepatocytes. The results of the mechanistic studies showed that SCLP upregulated Nrf2 expression, promoted Nrf2 nuclear translocation, and enhanced the ability of Nrf2 to bind antioxidant response elements (AREs). Furthermore, SCLP activated Nrf2-ARE pathway, thus upregulating the expression of oxidative stress-related proteins (HO-1, NQO-1 and GCLC). In conclusion, this study confirmed the close correlation between liver protection by SCLP upon exposure to APAP and activated of the Nrf2-ARE pathway. These findings suggest that SCLP is an attractive therapeutic candidate drug for the treatment of AILI.